Praktik kepemimpinan kepala sekolah dalam meningkatkan kinerja guru di SD Negeri 4 Kalibogor - Maghfirah, Khairina; Aliyah, Avina Faizatul (Maliki Interdisciplinary Journal, 2025)
Teacher performance is one of the determining factors of the quality of education in elementary schools. This study examines the leadership practices of the principal in improving teacher performance at SD Negeri 4 Kalibogor. The study was conducted using a descriptive qualitative approach, with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the principal plays a central role in building a positive work climate, establishing a clear school vision and mission, and establishing harmonious working relationships with teachers. The strategies implemented include teacher empowerment, involvement in decision-making, academic supervision, and providing appreciation for work achievements. These leadership practices have a positive impact on improving teacher discipline, motivation, and professional responsibility. Thus, the effectiveness of the principal's leadership is proven to contribute directly to improving teacher performance in elementary schools.